Preparation method and application of wide-spectrum response type Bi19S27Br3 / Bi3O4Br heterojunction photocatalysis
By preparing a Bi19S27Br3/Bi3O4Br heterojunction photocatalyst, the problem of low catalytic efficiency in the photocatalytic CO2 reduction system was solved, achieving efficient and selective CO2 reduction to CO and improving solar energy utilization efficiency.
Patent Information
- Application Number
- CN202511016877.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-23
- Publication Date
- 2025-11-04
AI Technical Summary
The existing photocatalytic CO2 reduction systems suffer from low catalytic efficiency and poor selectivity, mainly due to insufficient photon utilization, easy recombination of photogenerated electrons and holes, and the limited spectral response and insufficient surface adsorption activation capabilities of materials such as BiOBr in visible light-driven catalytic systems.
Bi19S27Br3/Bi3O4Br heterojunction photocatalysts were prepared by electrochemical deposition and vapor-phase sulfidation to form a tightly bound heterojunction interface. By utilizing the broad spectral response and photothermal synergistic effect, the charge separation efficiency and catalytic activity were improved.
This method achieves efficient reduction of CO2 to CO without precious metal co-catalysts, improving solar energy utilization efficiency, broadening the spectral response range, and enhancing the stability and activity of the catalyst.
Smart Images

Figure CN120885245A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to a wide-spectrum response type Bi 19 S 27 Preparation method and application of Br3 / Bi3O4Br heterojunction photocatalysis, belong to the field of photocatalytic carbon reduction energy conversion. BACKGROUND
[0002] With the increasingly serious problem of climate change caused by greenhouse gas emissions, under the driving of the strategic targets of "carbon neutralization" and "carbon peak", how to realize the resource conversion of CO2 has become an important research direction in the current field of materials and energy. Photocatalytic technology, as a green, mild and sustainable means of solar energy utilization, can reduce CO2 to CO or other hydrocarbons without high temperature and high pressure, and is considered as a promising carbon cycle path.
[0003] However, the current photocatalytic CO2 reduction system generally has low catalytic efficiency and poor selectivity, the main reasons are as follows: first, most single photocatalysts have limited response ability to visible light and near-infrared light, resulting in insufficient photon utilization; second, photo-generated electrons and holes are easy to recombine, resulting in low charge separation efficiency and serious reaction path competition, which cannot effectively drive the subsequent redox reaction. In order to solve the above problems, researchers widely pay attention to the design of semiconductor heterojunction. Among them, bismuth-based oxyhalides (such as BiOCl, BiOBr, BiOI, etc.) have excellent performance in visible light driven catalytic system due to their layered structure, moderate band gap and high chemical stability. For example, bismuth oxybromide (BiOBr) has been widely concerned due to its unique layered structure and certain visible light response ability. However, when BiOBr is applied to photocatalytic CO2 reduction, its inherent defects seriously limit the further improvement of performance. Specifically, first, it is a single valence Bi 3+ structure, lacking the ability to regulate valence; second, its band gap is relatively wide (about 2.7eV), and the absorption range is mainly limited to ultraviolet to short-wave visible light, making it difficult to efficiently utilize medium and long-wave visible light and near-infrared region; in addition, the oxygen vacancy concentration in BiOBr is low, and the surface adsorption and activation ability of CO2 is limited, which restricts the overall performance improvement of BiOBr in CO2 reduction reaction. Therefore, it is urgent to develop alternative materials with more optimal electronic structure, wider spectral response ability and stronger reaction activity for constructing new high-efficiency heterojunction photocatalysts.
[0004] In order to overcome the limitations of single material, another technical route is to combine bismuth-based oxyhalides with bismuth-based sulfides with narrow band gap (such as Bi2S3, Bi 19 S 27complexation of Br3, etc., to construct a heterojunction. In theory, this strategy can expand the spectral response range through band matching, while promoting charge separation using the built-in electric field at the interface. However, this simple physical complexation or heterojunction constructed by traditional methods often faces new challenges: on the one hand, bismuth-based sulfides themselves are poor in stability and short in lifetime during the reaction process; on the other hand, it is difficult to construct a heterojunction with stable structure and close contact through a "two-step solvothermal method" (i.e., first preparing two materials separately and then preparing by solvothermal method), and defects existing at the interface will become the center of charge recombination, which is not conducive to carrier migration. In addition, how to accurately control the proportion and interface structure of the two phases to achieve the best synergistic catalytic effect has so far been a technical difficulty that has not been effectively solved in this field.
[0005] In summary, there is an urgent need in the prior art for a new type of photocatalyst that meets the following conditions: (1) has a wide spectral response capability covering the visible light to near-infrared region; (2) has efficient charge separation and transport efficiency to suppress carrier recombination; (3) has a high stability structure and controllable, high-quality heterojunction interface. SUMMARY
[0006] The present application aims to overcome the shortcomings of the prior art and provide a gas-phase assisted electrochemical multi-step synthesis of Bi 19 S 27 Br3 / Bi3O4Br heterojunction photocatalyst. By controlling the conditions of electrochemical deposition and gas-phase sulfidation, the present application prepares a Bi 19 S 27 Br3 / Bi3O4Br heterojunction powder photocatalyst for efficient visible light catalytic reduction of CO2 to CO.
[0007] To achieve the above-mentioned purposes, the present application adopts the following technical solutions: (1) Electrochemical deposition of precursor film: place a three-electrode system in an electrolyte containing soluble bismuth salt and bromide for electrodeposition to form a Bi3O4Br precursor film on the working electrode.
[0008] (2) Gas-phase sulfidation treatment: the method of gas-phase sulfidation treatment is one of the following methods, Method 1: place the working electrode with the deposited Bi3O4Br precursor film obtained in step (1) in a tube furnace, exhaust the air in the furnace with an inert gas, heat the tube furnace to a preset sulfidation reaction temperature, continuously introduce a mixed gas composed of H2S and inert gas into the furnace to carry out gas-phase sulfidation reaction under the condition of keeping the reaction temperature constant, stop the gas and heating after the reaction is completed, and the heterojunction structure film can be obtained on the working electrode after natural cooling.
[0009] Method two: Put sulfur powder in the upstream area of the reaction tube, use inert gas to exhaust the air in the furnace, continue to heat the sulfur powder under the protection of inert gas to make it gasify, at the same time, put the working electrode sample on which the Bi3O4Br precursor thin film is deposited obtained in step (1) in the downstream heating area, stop the ventilation and heating after the reaction is completed, and the heterojunction structure thin film on the working electrode can be obtained after natural cooling.
[0010] (3) Powdering: Put the Bi3O4Br thin film obtained in step (2) into a mortar, add a certain amount of alcohol, and grind the film into powder. 19 S 27 Mechanically peel or scrape the Bi3O4Br / BiBr3 heterojunction structure thin film from the working electrode, and collect the Bi3O4Br / BiBr3 heterojunction powder precursor. 19 S 27 Br3 / Bi3O4Br heterojunction powder precursor.
[0011] (4) Annealing treatment: Heat treat the Bi3O4Br / BiBr3 heterojunction powder precursor obtained in step (3) in inert gas, and then cool it down with the furnace to obtain the target Bi3O4Br / BiBr3 heterojunction photocatalyst powder. 19 S 27 Br3 / Bi3O4Br heterojunction powder precursor. 19 S 27 Br3 / Bi3O4Br heterojunction photocatalyst powder.
[0012] Preferably, the electrolyte in step (1) contains 0.01-0.03 mol / L of soluble bismuth salt and 0.05-0.2 mol / L of bromide, the soluble bismuth salt is selected from at least one of bismuth nitrate, bismuth chloride or bismuth sulfate; the bromide is selected from at least one of sodium bromide, potassium bromide or ammonium bromide; the acidity of the electrolyte is adjusted to pH 1-2; the corresponding potential is -0.1 to -0.3 V, and the deposition time is 10-15 minutes.
[0013] Preferably, in the three-electrode system in step (1), the FTO conductive glass is the working electrode, the platinum electrode is the counter electrode, and the Ag / AgCl electrode is the reference electrode.
[0014] Preferably, in method one and method two in step (2), the inert gas is nitrogen or argon.
[0015] Preferably, in method one of step (2), the preset sulfidation reaction temperature is 300-400°C, and the time for passing H2S gas to perform sulfidation reaction is 1-3 hours.
[0016] Preferably, in method one of step (2), the volume of H2S gas accounts for 5%-20% of the volume of the mixed gas, and the gas flow of H2S is 20-100 sccm.
[0017] Preferably, the temperature of the sulfur powder gasification in method two of step (2) is 200-250 DEG C, the heating temperature of the sample area is 250-300 DEG C, and the reaction time is 2-4 hours.
[0018] Preferably, the film-removing process in step (3) can be carried out by mechanical grinding with the aid of ethanol, and impurities are removed by centrifugation and ethanol cleaning.
[0019] Preferably, the annealing conditions in step (4) are as follows: the temperature is 300-400 DEG C, and the holding time is 1-4 hours.
[0020] The wide-spectrum response type Bi 19 S 27 Application of Br3 / Bi3O4Br heterojunction photocatalytic material in catalyzing CO2 reduction reaction to generate CO.
[0021] The present application has the following advantages: (1) Hierarchical utilization of wide spectrum: the heterojunction material is composed of Bi3O4Br and Bi 19 S 27 Br3, and the absorption range is widened; in addition, the heterojunction structure can utilize the wide spectrum sunlight in layers, i.e., the carrier is excited by UV-Vis, and the catalyst surface temperature is in-situ increased by IR, which is of great value for improving the overall efficiency of solar energy utilization and promoting the application of photocatalytic technology; the near-infrared absorption characteristics of Bi 19 S 27 Br3 make the local temperature of the material rise during illumination, forming a micro-thermal field, which helps to enhance the adsorption and activation of CO2.
[0022] (2) In-situ heterojunction formation: Bi 19 S 27 Br3 is generated on the Bi3O4Br thin film by partial sulfidation, and the two phases are tightly combined to form a 1D-2D heterojunction interface; compared with simple mechanical mixing or two-step hydrothermal method, the heterojunction is more firm, and the charge transfer at the interface is smoother, which is beneficial to the separation of photo-generated carriers.
[0023] (3) The heterojunction structure exhibits obvious photo-thermal synergistic effect, near-infrared light is effectively absorbed and converted into heat energy, which promotes the catalytic reaction kinetics under the action of local temperature rise, and further improves the separation efficiency of photo-generated carriers, thereby enhancing the overall photocatalytic performance.
[0024] (4) Without introducing noble metal cocatalysts or sacrificial agents, high selectivity and high yield photocatalytic reduction of CO2 is realized, and the experimental results show that the overall catalytic performance is better than that of the reported Bi 19 S 27 Br3 / BiOBr system.
[0025] (5) Strong controllability of process: the multi-step synthesis strategy has good repeatability and is suitable for large-scale preparation. The material synthesis adopts electrochemical deposition combined with gas-phase sulfurization process, which has the characteristics of controllable reaction conditions, clear process route, and uniformly dense heterojunction prepared, and is suitable for practical application and promotion.
[0026] (6) Photocatalytic performance: thanks to the above structural advantages, the heterojunction photocatalyst obtained by the application has high activity and high selectivity for the reduction of CO2 under wide spectrum. CO2 can be efficiently reduced to CO without the help of catalyst, which improves the solar energy utilization efficiency and has important significance for the resource utilization of CO2. BRIEF DESCRIPTION OF DRAWINGS
[0027] Figure 1 X-ray diffraction (XRD) patterns of the samples prepared in Example 1 and Comparative Examples 1-4.
[0028] Figure 2 Absorption (DRS) test graphs of the samples prepared in Example 1 and Comparative Examples 1-4.
[0029] Figure 3 Photothermal effect graphs of the samples prepared in Example 1 and Comparative Examples 1-4 under full spectrum irradiation.
[0030] Figure 4 Comparison graph of the photo-thermal conversion efficiency of the samples prepared in Example 1, Comparative Example 3 and Comparative Example 4 under 850 nm single-band near-infrared light irradiation.
[0031] Figure 5 SEM graph of the sample prepared in Example 1.
[0032] Figure 6 EPR test graphs of Example 1 and Comparative Examples 1, 3 and 4.
[0033] Figure 7 Photocatalytic activity graph of the samples prepared in Example 1 and Comparative Examples 1-4.
[0034] Figure 8 Photocatalytic activity cycle experiment of Example 1. DETAILED DESCRIPTION
[0035] The preparation method steps of the application will be described in detail below in conjunction with specific examples. It should be understood that these examples are used to illustrate the application rather than limit the scope of the application, and those skilled in the art can adjust the process parameters according to actual needs without departing from the spirit of the application.
[0036] Example 1 A wide-spectrum response type Bi 19 S27 A method for preparing a Br3 / Bi3O4Br heterojunction photocatalytic material is described as follows: (1) Electrochemical deposition of Bi3O4Br precursor film: First, a 1 cm x 2 cm FTO conductive glass was sequentially placed in anhydrous ethanol and deionized water, each ultrasonically cleaned for 15 minutes, then blown dry with a high-purity nitrogen stream for standby, then the electrolyte was prepared, 1.5 mmol of bismuth nitrate pentahydrate (Bi(NO3)3·5H2O) and 3.0 mmol of sodium bromide (NaBr) were dissolved in 50 mL of deionized water to prepare an aqueous solution containing 0.03 mol / L Bi(NO3)3·5H2O and 0.06 mol / L NaBr, 1 mol / L dilute nitric acid (HNO3) was added dropwise to the above solution, and the pH was monitored with a pH meter, and the pH of the electrolyte was accurately adjusted to 1.5. Finally, electrochemical deposition was carried out in a standard three-electrode system electrolytic cell, in which the pretreated FTO conductive glass was used as the working electrode, the platinum electrode was used as the counter electrode, and the Ag / AgCl electrode (saturated KCl solution) was used as the reference electrode; the three electrodes were immersed in the prepared electrolyte, and the deposition was carried out at room temperature (25°C) under static conditions by constant potential method; the deposition potential was set to -0.2 V (vs. Ag / AgCl), and the deposition time was 15 minutes; after deposition, the FTO substrate with the thin film was taken out, washed repeatedly with deionized water, and naturally air-dried to obtain an FTO conductive glass containing a Bi3O4Br precursor film.
[0037] (2) Gas phase sulfidation treatment: the FTO conductive glass containing the Bi3O4Br precursor film obtained in step (1) was placed in the central position of the tube furnace, first, high-purity argon (Ar) gas with a flow rate of 200 sccm was introduced into the tube furnace for 30 minutes to completely exhaust the air in the furnace, then the tube furnace was heated to 400°C at a heating rate of 5°C / min, after the temperature was stable, the gas source was switched to a mixed gas of H2S and argon (Ar), the volume fraction of H2S gas was 10% of the mixed gas, and the total gas flow rate was controlled at 100 sccm, under this gas and temperature, the gas phase sulfidation reaction was carried out, the constant temperature time was 3 hours, after the reaction was completed, the H2S gas source was immediately closed, and pure argon gas was switched and kept flowing until the tube furnace naturally cooled to room temperature, finally, an FTO substrate containing a Bi3O4Br heterojunction structure film was obtained. 19 S 27 Br3 / Bi3O4Br heterojunction structure film.
[0038] (3) Detachment and powdering: The heterojunction film obtained in step (2) was placed together with the FTO substrate in an agate mortar, and a small amount of anhydrous ethanol was added dropwise for wetting. A clean medicine spoon was used to detach the heterojunction film from the FTO substrate, and then the film was ground thoroughly until a uniform fine powder was formed.
[0039] (4) Annealing treatment: The fine powder obtained in step (3) was transferred to a porcelain boat and placed in the center of a tube furnace. Under the protection of high-purity argon gas (flow rate 100 sccm), the temperature was raised to 400°C at a rate of 5°C / min, and the temperature was kept constant for 2 hours. After the end of the constant temperature holding, the furnace was naturally cooled to room temperature under argon protection. The final powder obtained was Bi 19 S 27 Br3 / Bi3O4Br heterojunction photocatalyst.
[0040] The sample prepared in this example is named Bi 19 S 27 Br3 / Bi3O4Br-gas phase assisted electrochemical method.
[0041] Example 2 A wide-spectrum response type Bi 19 S 27 The preparation method of the Bi (1) Electrochemical deposition of Bi3O4Br precursor film: First, a 1 cm x 2 cm FTO conductive glass was sequentially placed in anhydrous ethanol and deionized water and ultrasonically cleaned for 15 minutes each, and then dried with a high-purity nitrogen gas stream for standby use. Next, the electrolyte was prepared. In a beaker, 1.5 mmol of bismuth chloride (BiCl3) and 3.0 mmol of potassium bromide (KBr) were dissolved in 50 mL of deionized water to prepare an aqueous solution containing 0.03 mol / L of BiCl3 and 0.06 mol / L of KBr; 1 mol / L dilute nitric acid (HNO3) was added dropwise to the above solution, and a pH meter was used to monitor and accurately adjust the pH value of the electrolyte to 2; finally, electrochemical deposition was performed in an electrolytic cell of a standard three-electrode system. The pretreated FTO conductive glass was used as the working electrode, a platinum electrode was used as the counter electrode, and an Ag / AgCl electrode (saturated KCl solution) was used as the reference electrode; the three electrodes were immersed in the prepared electrolyte, and deposition was carried out at room temperature (25°C) under static conditions using a constant potential method. The deposition potential was set to -0.1 V (vs. Ag / AgCl), and the deposition time was 10 minutes; after the deposition was completed, the FTO substrate with the attached film was repeatedly washed with deionized water and naturally dried in air to obtain the FTO conductive glass containing the Bi3O4Br precursor film.
[0042] (2) Vapor phase sulfuration treatment (sulfur powder vaporization): Put the porcelain boat containing 0.5 g of sulfur powder into the upstream heating zone of the tube furnace, and put the FTO conductive glass containing the Bi3O4Br precursor film obtained in step (1) into the downstream heating zone of the tube furnace; first, introduce high-purity argon (Ar) gas into the tube furnace at a flow rate of 200 sccm for 30 minutes to completely exhaust the air in the furnace; then, while continuously introducing high-purity argon as a carrier gas at a flow rate of 100 sccm, start the programmed temperature rise at a rate of 5°C / min; heat the temperature of the region where the sulfur powder is located to 220°C and keep it constant, so that it evaporates to form sulfur vapor; at the same time, heat the temperature of the region where the sample is located to 280°C and keep it constant; carry out the vapor phase sulfuration reaction under the above conditions, and the constant temperature time is 3 hours. After the reaction is completed, stop heating and naturally cool to room temperature under the protection of argon gas; finally, the FTO substrate containing the Bi 19 S 27 Br3 / Bi3O4Br heterojunction structure film is obtained.
[0043] (3) Film removal and powder preparation: Put the heterojunction film obtained in step (2) together with the FTO substrate into an agate mortar, add a small amount of anhydrous ethanol for wetting; use a clean medicine spoon to separate the heterojunction film from the FTO substrate, then grind thoroughly until a uniform fine powder is formed.
[0044] (4) Annealing treatment: Transfer the powder obtained in step (3) to a porcelain boat and place it in the center of the tube furnace. Under the protection of high-purity argon gas (flow rate 100 sccm), heat to 300°C at a rate of 5°C / min, and keep the temperature constant at this temperature for 4 hours; after the constant temperature treatment is completed, naturally cool to room temperature under the protection of argon gas. The powder obtained finally is the Bi 19 S 27 Br3 / Bi3O4Br heterojunction photocatalytic material prepared by vapor phase assisted electrochemical method.
[0045] Example 3 A wide-spectrum response type Bi 19 S 27 Br3 / Bi3O4Br heterojunction photocatalytic material is prepared by the following steps: (1) Electrochemical deposition of Bi3O4Br precursor film: First, a piece of 1 cm x 2 cm FTO conductive glass was sequentially placed in anhydrous ethanol and deionized water, each ultrasonic cleaning for 15 minutes, then dried with a high-purity nitrogen stream for standby, then the electrolyte was prepared, 1.5 mmol of bismuth sulfate (Bi2(SO4)3) and 6.0 mmol of ammonium bromide (NH4Br) were dissolved in 50 mL of deionized water to prepare an aqueous solution containing 0.03 mol / L Bi2(SO4)3 and 0.12 mol / L NH4Br, 1 mol / L dilute nitric acid (HNO3) was added dropwise to the above solution, and the pH was monitored with a pH meter, and the pH of the electrolyte was accurately adjusted to 1. Finally, electrochemical deposition was carried out in a standard three-electrode system electrolytic cell, in which the pretreated FTO conductive glass was used as the working electrode, the platinum electrode was used as the counter electrode, and the Ag / AgCl electrode (saturated KCl solution) was used as the reference electrode; the three electrodes were immersed in the prepared electrolyte, and the deposition was carried out at room temperature (25°C) under static conditions by constant potential method. The deposition potential was set to -0.3 V (vs. Ag / AgCl), and the deposition time was 15 minutes; after deposition, the FTO substrate with a thin film was taken out, washed repeatedly with deionized water, and naturally dried in air to obtain an FTO conductive glass containing a Bi3O4Br precursor thin film.
[0046] (2) Gas phase sulfidation treatment: the FTO conductive glass containing the Bi3O4Br precursor thin film obtained in step (1) was placed in the central position of the tube furnace, first, high-purity argon (Ar) with a flow rate of 200 sccm was introduced into the tube furnace for 30 minutes to completely exhaust the air in the furnace, then the tube furnace was heated to 400°C at a heating rate of 5°C / min, after the temperature was stable, the gas source was switched to a mixed gas of H2S and argon (Ar), the volume fraction of H2S gas was 10% of the mixed gas, and the total gas flow rate was controlled at 100 sccm. Under this gas and temperature, gas phase sulfidation reaction was carried out, the constant temperature time was 3 hours, after the reaction was completed, the H2S gas source was immediately closed, and pure argon gas was switched and kept flowing until the tube furnace naturally cooled to room temperature, finally the FTO substrate containing the Bi 19 S 27 Br3 / Bi3O4Br heterojunction structure thin film was obtained.
[0047] (3) Film removal and powder preparation: the heterojunction thin film obtained in step (2) together with the FTO substrate was placed in an agate mortar, and a small amount of anhydrous ethanol was added for wetting. The heterojunction thin film was peeled off from the FTO substrate using a clean medicine spoon, and then thoroughly ground until a uniform fine powder was formed.
[0048] (4) Annealing treatment: the fine powder obtained in step (3) was transferred into a porcelain boat and placed in the center of a tube furnace, and heated to 400°C at a heating rate of 5°C / min under the protection of high-purity argon gas (flow rate 100 sccm), and kept at this temperature for 2 hours, and after the end of the heat preservation, it was naturally cooled to room temperature in the furnace under the protection of argon. The final powder obtained is Bi 19 S 27 Br3 / Bi3O4Br-gas phase assisted electrochemical method.
[0049] It was detected that the Bi 19 S 27 The performance of the Br3 / Bi3O4Br heterojunction photocatalyst is similar to that of Example 1.
[0050] Comparative Example 1 A preparation method of a Bi3O4Br photocatalytic material, the preparation method of the comparative example is exactly the same as steps (1), (3) and (4) in Example 1, but does not go through the step (2) of gas phase sulfidation treatment, the specific steps are as follows: (1) Electrochemical deposition of Bi3O4Br precursor film: first, a 1 cm x 2 cm FTO conductive glass was sequentially placed in anhydrous ethanol and deionized water, each was ultrasonically cleaned for 15 minutes, then dried with a high-purity nitrogen gas stream for standby, then the electrolyte was prepared, in a beaker, 1.5 mmol of bismuth nitrate pentahydrate (Bi(NO3)3·5H2O) and 3.0 mmol of sodium bromide (NaBr) were dissolved in 50 mL of deionized water to prepare an aqueous solution containing 0.03 mol / L of Bi(NO3)3·5H2O and 0.06 mol / L of NaBr; 1 mol / L of dilute nitric acid (HNO3) was added dropwise to the above solution, and a pH meter was used to monitor and accurately adjust the pH value of the electrolyte to 1.5; finally, electrochemical deposition was carried out in a standard three-electrode system electrolytic cell; the pretreated FTO conductive glass was used as the working electrode, the platinum electrode was used as the counter electrode, and the Ag / AgCl electrode (saturated KCl solution) was used as the reference electrode; the three electrodes were immersed in the above prepared electrolyte, and the deposition was carried out at room temperature (25°C) under static conditions by using constant potential method. The deposition potential was set to -0.2 V (vs. Ag / AgCl), and the deposition time was 10 minutes; after the deposition was completed, the FTO substrate with the film was taken out, washed repeatedly with deionized water, and naturally dried in air to obtain an FTO conductive glass containing a Bi3O4Br precursor film.
[0051] (2) Delamination and powdering: Put the Bi3O4Br film obtained in step (1) together with the FTO substrate into an agate mortar, and add a small amount of anhydrous ethanol to wet it; use a clean medicine spoon to separate the Bi3O4Br film from the FTO substrate, and then grind it thoroughly until a uniform fine powder is formed.
[0052] (3) Annealing treatment: Put the powder obtained in step (2) into a tube furnace, heat it to 400°C at a heating rate of 5°C / min under the protection of high-purity argon gas, and keep it at this temperature for 2 hours; after the heat preservation is completed, cool it to room temperature naturally in the furnace under the protection of argon. The final powder obtained is the sample of Comparative Example 1.
[0053] The sample prepared in this comparative example is named Bi3O4Br.
[0054] Comparative Example 2 A kind of wide spectrum response type Bi 19 S 27 Br3 photocatalytic material preparation method, the preparation method of this comparative example is exactly the same as steps (1), (3) and (4) in Example 1, but step (2) is changed to complete gas phase sulfuration treatment, the specific steps are as follows: (1) Electrochemical deposition of Bi3O4Br precursor film: First, a 1 cm x 2 cm FTO conductive glass is sequentially placed in anhydrous ethanol and deionized water, each ultrasonic cleaning for 15 minutes, then dried with a stream of high-purity nitrogen gas, then the electrolyte is prepared, in a beaker, 1.5 mmol of bismuth nitrate pentahydrate (Bi(NO3)3·5H2O) and 3.0 mmol of sodium bromide (NaBr) are dissolved in 50 mL of deionized water to prepare an aqueous solution containing 0.03 mol / L Bi(NO3)3·5H2O and 0.06 mol / L NaBr. Add a few drops of concentrated nitric acid (HNO3) with a concentration of 1 mol / L to the above solution, and monitor with a pH meter to accurately adjust the pH of the electrolyte to 1.5; finally, electrochemical deposition is carried out in a standard three-electrode system electrolytic cell; the pretreated FTO conductive glass is used as the working electrode, the platinum electrode is used as the counter electrode, and the Ag / AgCl electrode (saturated KCl solution) is used as the reference electrode; immerse the three electrodes in the prepared electrolyte, and carry out deposition at room temperature (25°C) under static conditions by constant potential method. The deposition potential is set to -0.2 V (vs. Ag / AgCl), and the deposition time is 10 minutes; after deposition, the FTO substrate with the film is taken out, washed repeatedly with deionized water, and naturally dried in air to obtain the FTO conductive glass containing the Bi3O4Br precursor film.
[0055] (2) Complete gas phase sulfuration treatment: The FTO conductive glass with Bi3O4Br precursor film obtained in step (1) was placed in a tube furnace. It was heated to 400°C in high-purity argon gas. After the temperature was stabilized, Ar / H2S mixed gas with a volume fraction of 10% H2S was introduced. To ensure that the Bi3O4Br precursor film was converted into Bi 19 S 27 Br3 as completely as possible, the constant temperature time of the vapor phase sulfidation reaction was extended to 8 hours. After the reaction was completed, the reaction system was naturally cooled to room temperature under pure argon protection.
[0056] (3) Film removal and powdering: the heterojunction film obtained in step (2) was placed in a marver mortar together with the FTO substrate, and a small amount of anhydrous ethanol was added for wetting. A clean medicine spoon was used to separate the heterojunction film from the FTO substrate, and then the heterojunction film was ground thoroughly until a uniform fine powder was formed.
[0057] (4) Annealing treatment: the powder obtained in step (3) was placed in a tube furnace and heated to 400°C at a heating rate of 5°C / min under high-purity argon gas protection, and then kept at this temperature for 2 hours. After the constant temperature treatment was completed, the system was naturally cooled to room temperature in argon protection. The final obtained powder was the sample of Comparative Example 2.
[0058] The sample prepared in this comparative example was named Bi 19 S 27 Br3.
[0059] Comparative Example 3 A method for preparing a Bi 19 S 27 Br3 / Bi3O4Br heterojunction photocatalytic material with a wide spectrum response: (1) 0.025 mmol of Bi(NO2)3·5H2O, 0.4 mmol of Bi3O4Br, 0.2 mmol of [C 16mim ]Br (1-hexadecyl-3-methyl imidazole bromide), and 0.7 mmol of thiourea were weighed and mixed in 30 ml of ethylene glycol. After being stirred uniformly, the mixture was ultrasonically treated for 8 min under a power of 80 W. The mixture was then transferred to a polytetrafluoroethylene reaction kettle, and the reaction temperature was 130°C. The reaction lasted for 12 h. After the precipitation was filtered, it was washed with deionized water and anhydrous ethanol three times each, and then dried at 70°C for 12 h. The final obtained powder was the sample of Comparative Example 3.
[0060] The sample prepared in this comparative example was named Bi 19 S 27 Br3 / Bi3O4Br prepared by a hydrothermal method.
[0061] Comparative Example 4 A Bi 19 S 27 A preparation method of a Br3 / BiOBr heterojunction photocatalytic material, and the specific steps are as follows: (1) Electrochemical deposition of BiOBr precursor film: first, a 1 cm x 2 cm FTO conductive glass was sequentially placed in anhydrous ethanol and deionized water, each ultrasonic cleaning for 15 minutes, then dried with a high-purity nitrogen gas flow for standby. Next, the electrolyte was prepared, 2.0 mmol of bismuth nitrate pentahydrate (Bi(NO3)3·5H2O) and 2.0 mmol of sodium bromide (NaBr) were dissolved in 50 mL of deionized water to prepare a Bi(NO3)3·5H2O and NaBr aqueous solution containing 0.04 mol / L; 1 mol / L dilute nitric acid (HNO3) was added dropwise to the above solution, and a pH meter was used to monitor and accurately adjust the pH value of the electrolyte to 0.8; finally, electrochemical deposition was carried out in an electrolytic cell of a standard three-electrode system; the pretreated FTO conductive glass was used as the working electrode, the platinum electrode was used as the counter electrode, and the Ag / AgCl electrode (saturated KCl solution) was used as the reference electrode; the three electrodes were immersed in the prepared electrolyte, and the deposition was carried out at room temperature (25°C) under static conditions by using the constant potential method. The deposition potential was set to -0.05 V (vs. Ag / AgCl), and the deposition time was 5 minutes; after deposition, the FTO substrate with a thin film was taken out, washed repeatedly with deionized water, and naturally dried in air to obtain an FTO conductive glass containing a BiOBr precursor film.
[0062] (2) Gas phase sulfidation treatment: a porcelain boat containing 0.5 g of sulfur powder was placed in the upstream heating zone of the tube furnace, and the FTO conductive glass containing the BiOBr precursor film obtained in step (1) was placed in the downstream heating zone of the tube furnace. First, high-purity argon (Ar) gas with a flow rate of 200 sccm was introduced into the tube furnace for 30 minutes to completely exhaust the air in the furnace; then, while continuously introducing high-purity argon as a carrier gas with a flow rate of 100 sccm, the temperature was programmed to rise at a rate of 5°C / min. The temperature of the region containing sulfur powder was heated and maintained at 180°C to evaporate sulfur vapor; at the same time, the temperature of the region containing the sample was heated and maintained at 230°C; under the above conditions, the gas phase sulfidation reaction was carried out, and the constant temperature time was 1.5 hours; after the reaction was completed, the heating was stopped, and the furnace was naturally cooled to room temperature under the protection of argon gas; finally, an FTO substrate containing a Bi 19 S 27 Br3 / BiOBr heterojunction structure film was obtained.
[0063] (3) Demolding and powdering: Place the heterojunction film obtained in step (2) together with the FTO substrate in an agate mortar and add a small amount of anhydrous ethanol to wet it; use a clean spatula to peel the heterojunction film off the FTO substrate and then grind it thoroughly until a uniform fine powder is formed.
[0064] (4) Annealing treatment: The powder obtained in step (3) is transferred to a ceramic boat and placed in the center of a tube furnace; under the protection of high-purity argon gas (flow rate 100 sccm), it is heated to 250°C at a heating rate of 5°C / min and held at this temperature for 5 hours; after the holding period, it is naturally cooled to room temperature under the protection of argon gas. The final powder obtained is the target heterojunction photocatalyst.
[0065] The sample prepared in this comparative example was named Bi. 19 S 27 Br3 / BiOBr-gas phase-assisted electrochemical method.
[0066] Performance testing: The materials prepared in Example 1 and Comparative Examples 1 to 4 were subjected to relevant performance tests. First, X-ray diffraction analysis was performed on the prepared materials, and the results are as follows: Figure 1 As shown in the figure, it can be observed that the prepared samples correspond to Bi. 19 S 27 The standard PDF cards for Br3 (JCPDS NO.26-0813) and Bi3O4Br (JCPDS NO.84-0793) were used. It is noteworthy that no diffraction impurities were observed in the diffraction pattern. Further observation of the magnified crystal plane images revealed that the Bi3O4Br prepared in Example 1... 19 S 27 The diffraction peaks of Br3 / Bi3O4Br shifted to a larger angle, indicating that Bi atoms were successfully introduced into the interface as shared bridges, causing lattice distortion.
[0067] like Figure 2 As shown, compared with a single catalyst, the heterojunction synthesized by gas-phase assisted electrochemical multi-step synthesis has a wider absorption range and greater intensity. The heterojunction prepared in Example 1 has a higher response intensity than the absorption spectrum curves of Comparative Examples 1-4.
[0068] like Figure 3 As shown, a photothermal effect test was conducted using a 300W xenon lamp (CEL-LAX500). The samples were evaluated for light-to-heat conversion capability; the reactor used was a customized crucible with a volume of 3 mL, 100 mg of sample was added to the crucible, and placed in a light-dark environment for 5 min, and analyzed periodically by an infrared thermal imager (HIKMICRO H10); the test results showed that the light-to-heat performance of Example 1 was improved compared to the full-spectrum irradiation of Comparative Examples 1-4, the heterojunction photocatalyst of Example 1 can more effectively utilize near-infrared light, and has good light-to-heat conversion effect.
[0069] As shown in Figure 4 , the light-to-heat conversion efficiency of the materials prepared in Example 1 and Comparative Examples 3 and 4 under 850 nm single-band near-infrared light irradiation can be found that the light-to-heat conversion efficiency of the material prepared in Example 1 is higher than that of Comparative Example 3 and Comparative Example 4, indicating that Example 1 has better light-to-heat conversion utilization efficiency.
[0070] As shown in Figure 5 , the scanning electron microscope (SEM) observation of the material prepared in Example 1 showed that the sample obtained after the gas phase assisted electrochemical multi-step treatment presented a mixed structure of rods and sheets; a part of the material showed a sheet-like layered Bi3O4Br structure, and another part was dominated by rod-like Bi S 19 S 27 Br3 crystals; it is speculated that the sheet-like Bi3O4Br is directionally converted under the action of sulfur gas at high temperature during the sulfuration process, and the generated Bi 19 S 27 Br3 preferentially grows on the surface or cracking area of Bi3O4Br in one-dimensional direction, forming a two-phase embedded heterostructure; the structure has a large specific surface area and a large heterojunction contact area, providing a favorable path for the effective separation of photo-generated carriers and interface reaction.
[0071] As shown in Figure 6 , the samples prepared in Example 1 and Comparative Examples 1, 3 and 4 were tested by electron paramagnetic resonance (EPR); the results showed that the EPR signal intensity of Example 1 was significantly higher than that of Comparative Examples 1, 3 and 4, indicating that it had more unpaired electrons or defect sites, indicating that the oxygen vacancy concentration or free radical content in the material was higher, which was beneficial to improve the photocatalytic activity; As shown in Figure 7 , the heterojunction material prepared in Example 1 of the present application showed excellent photocatalytic activity, and the CO generation rate (313.908 and 239.61 μmol g -1 h -1 , respectively) was much higher than that of Comparative Example 1 (Bi3O4Br, 40.855 μmol g -1 h -1 ) and Comparative Example 2 (Bi19 S 27 Br3, 58.955 μmol g -1 h -1 ), which is also superior to Comparative Example 3 (hydrothermal method) and Bi 19 S 27 Br3 / BiOBr heterojunction (239.61 μmol g -1 h -1 ), which proves the universality and superiority of the gas-phase assisted electrochemical method in constructing efficient heterojunctions. In particular, in different embodiments of the present application, Example 1 (Bi3O4Br as the substrate) as the preferred scheme exhibits the best catalytic activity, which is 1.31 times that of Comparative Example 4 (BiOBr as the substrate). This shows that the selection of Bi3O4Br as the substrate can bring unexpected performance gains, which is attributed to the change of its electronic structure and energy band position.
[0072] As Figure 8 shown, the material prepared in Example 1 was subjected to the photocatalytic reduction of CO2 cycle stability test, and it was found that after 6 cycles, the CO generation rate could still reach 261.163 μmol g -1 h -1 , about 83% of the first time, indicating that the Bi 19 S 27 Br3 / Bi3O4Br-gas-phase assisted electrochemical method exhibits high cycle stability.
[0073] In the description of the present specification, the description of the terms "one embodiment", "example", "specific example" and the like means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present application. In the present specification, the illustrative description of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.
[0074] The embodiments of the present application are described in detail above, but the present application is not limited to the described embodiments. For those skilled in the art, various changes, modifications, replacements and variations of the embodiments can be made without departing from the principles and spirits of the present application, and still fall within the protection scope of the present application.
Claims
1. A broadband responsive Bi 19 S 27 The method for preparing Br3 / Bi3O4Br heterojunction photocatalytic materials is characterized by: The preparation method is as follows: (1) Electrochemical deposition of precursor film: The three-electrode system is placed in an electrolyte containing soluble bismuth salt and bromide for electrodeposition to form Bi3O4Br precursor film on the working electrode; (2) Gas-phase sulfidation treatment: The gas-phase sulfidation treatment method is either Method 1 or Method 2. Method 1: Place the working electrode with Bi3O4Br precursor film deposited in step (1) into a tube furnace, exhaust the air in the furnace with inert gas, heat the tube furnace to the preset sulfidation reaction temperature, and continuously introduce a mixture of H2S and inert gas into the furnace to carry out the gas phase sulfidation reaction while keeping the reaction temperature constant. After the reaction is completed, stop the gas supply and heating, and after natural cooling, a heterojunction structure film can be obtained on the working electrode. Method 2: Place sulfur powder in the upstream area of the reaction tube, use inert gas to purge the air in the furnace, continue to heat the sulfur powder under the protection of inert gas to make it vaporize, and at the same time place the working electrode sample with Bi3O4Br precursor film deposited in step (1) in the downstream heating area. After the reaction is completed, stop the gas supply and heating, and after natural cooling, a heterojunction structure film can be obtained on the working electrode. (3) Demolding and powdering: Bi 19 S 27 The Br3 / Bi3O4Br heterojunction thin film was mechanically peeled off or ground and scraped from the working electrode to collect Bi. 19 S 27 Br3 / Bi3O4Br heterojunction powder precursor; (4) Annealing treatment: The Bi obtained in step (3) is annealed. 19 S 27 The Br3 / Bi3O4Br heterojunction powder precursor was heat-treated in an inert gas atmosphere and then cooled in the furnace to obtain the target Bi. 19 S 27 Br3 / Bi3O4Br heterojunction photocatalyst powder.
2. The broadband response type Bi according to claim 1 19 S 27 The method for preparing Br3 / Bi3O4Br heterojunction photocatalytic materials is characterized by: The electrolyte in step (1) contains 0.01–0.03 mol / L of soluble bismuth salt and 0.05–0.2 mol / L of bromide. The soluble bismuth salt is selected from at least one of bismuth nitrate, bismuth chloride, and bismuth sulfate. The bromide is selected from at least one of sodium bromide, potassium bromide, and ammonium bromide. The acidity of the electrolyte is adjusted to pH 1–2. The corresponding potential is -0.1–-0.3 V. The deposition time is 10–15 minutes.
3. The broadband responsive Bi according to claim 1 19 S 27 The method for preparing Br3 / Bi3O4Br heterojunction photocatalytic materials is characterized by: In step (1), the FTO conductive glass is the working electrode, the platinum electrode is the counter electrode, and the Ag / AgCl electrode is the reference electrode in the three-electrode system.
4. The broadband response type Bi according to claim 1 19 S 27 The method for preparing Br3 / Bi3O4Br heterojunction photocatalytic materials is characterized by: In step (2), the inert gas mentioned in method one and method two is nitrogen or argon.
5. The broadband response Bi according to claim 1 19 S 27 The method for preparing Br3 / Bi3O4Br heterojunction photocatalytic materials is characterized by: In step (2) of method one, the preset sulfidation reaction temperature is 300-400℃, and the time for introducing H2S gas to carry out the sulfidation reaction is 1-3 hours.
6. The broadband response Bi according to claim 1 19 S 27 The method for preparing Br3 / Bi3O4Br heterojunction photocatalytic materials is characterized by: In step (2) of method one, the volume of H2S gas accounts for 5% to 20% of the volume of the mixed gas, and the flow rate of H2S gas is 20 to 100 sccm.
7. The broadband response type Bi according to claim 1 19 S 27 The method for preparing Br3 / Bi3O4Br heterojunction photocatalytic materials is characterized by: In step (2) of method two, the temperature for sulfur powder gasification is 200-250℃, the heating temperature of the sample area is 250-300℃, and the reaction time is 2-4 hours.
8. The broadband response type Bi according to claim 1 19 S 27 The method for preparing Br3 / Bi3O4Br heterojunction photocatalytic materials is characterized by: The annealing conditions in step (4) are: temperature of 300-400℃ and holding time of 1-4 hours.
9. The broadband responsive Bi prepared according to claim 1 19 S 27 Application of Br3 / Bi3O4Br heterojunction photocatalytic material in catalyzing the reduction reaction of CO2 to CO.